Effective drought analysis by different methodological integrations in Yesilirmak Basin, Turkey - SERENCAM, UĞUR (My University, 2023)
Three different methodologies are integrated to identify hydrological drought characteristics in a drainage basin based on annual runoff discharge time series. First the cumulative distribution functions (CDFs) are identified by a set of risk levels for engineering water resources management. The standard precipitation index (SPI) is applied for \"normal\", \"moderately\", \"severely\" and \"extremely\" drought classification purpose. Regional drought assessment is accomplished by means of percentages of each drought class. For climate change impact assessment innovative trend analysis (ITA) is applied to SPI time series. The application of the methodology is presented for six sets of runoff data from the Northern Black Sea Yeilrmak drainage basin in Turkey. It is observed that each sub-drainage basin is subject to runoff volume reduction due to the climate change. The findings of this paper shed light on future similar studies by taking into account mentioned methodologies.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Engineering and Technology; ÇEVRE BİLİMLERİ; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); ENVIRONMENTAL SCIENCES; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); Doğa ve Peyzaj Koruma; Çevre Bilimi (çeşitli); Su Bilimi; Fizik Bilimleri; Yaşam Bilimleri; Nature and Landscape Conservation; Environmental Science (miscellaneous); Aquatic Science; Physical Sciences; Life Sciences; classification; drought; index; probability; runoff; risk; standard; trend; Turkey